A Commentary on Shareholder Derivative Litigation under the Companies and Allied Matters Act of Nigeria 2020. Issue 4 (September 2022) - Ubochioma, Wiseman
Abstract : On 7 August 2020, the President of the Federal Republic of Nigeria assented to the Companies and Allied Matters Bill which culminated in the Companies and Allied Matters Act of 2020. The new Act repeals the Companies and Allied Matters Act of 1990 which had been in operation for thirty years. The Act contains provisions that regulate the right of a party to institute an action for harm caused to a company by majority shareholders or directors, a principle of corporate law widely known as derivative suit. This article, therefore, examines the provisions of the Act. It argues that, unlike the 1990 Act, the provisions of the 2020 Act have achieved significant milestones in enhancement of the rights of minority shareholders, companies, directors and the roles of courts in shareholders' derivative litigation. However, there are gaps in the Act which may threaten the utility of derivative suits in corporate governance in Nigeria. The article suggests a hybrid of reforms to the Act and useful guides to courts that will be beneficial to shareholder applicants, directors and corporations in derivative litigation.